2020
DOI: 10.1097/hcr.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Use of Cardiac and Pulmonary Rehabilitation in Traditional and Community Settings

Abstract: Although both cardiac rehabilitation (CR) and pulmonary rehabilitation (PR) are recommended by clinical practice guidelines and covered by most insurers, they remain severely underutilized. To address this problem, the National Heart, Lung, and Blood Institute (NHLBI), in collaboration with the National Institute on Aging (NIA), developed Funding Opportunity Announcements (FOAs) in late 2017 to support Phase II clinical trials to increase the uptake of CR and PR in traditional and community settings. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Feasible population-specific strategies and additional timely research are needed to improve CR utilization and completion among these groups. 37,[57][58][59] Older adults may have distinctive challenges due to frailty, multimorbidity, cognitive decline, and other complexities associated with old age. 12 Finally, we concur with the recent call-to-action that "clinicians, health care leaders, and payers should prioritize incorporating CR as part of the standard of care for patients with HF."…”
Section: Discussionmentioning
confidence: 99%
“…Feasible population-specific strategies and additional timely research are needed to improve CR utilization and completion among these groups. 37,[57][58][59] Older adults may have distinctive challenges due to frailty, multimorbidity, cognitive decline, and other complexities associated with old age. 12 Finally, we concur with the recent call-to-action that "clinicians, health care leaders, and payers should prioritize incorporating CR as part of the standard of care for patients with HF."…”
Section: Discussionmentioning
confidence: 99%
“…We found that the percentage of CPET performed for cystic fibrosis was more than twice as large as for sickle cell disease, although there are an estimated 30,000 people in the United States with cystic fibrosis (32) and 100,000 with sickle cell disease (33). The data that could emanate from creating larger coalitions and consortia among pediatric CPET laboratories could also benefit ongoing national efforts to deal with pervasive disparities that continue to negatively affect healthcare across the country (34).…”
Section: Discussionmentioning
confidence: 99%
“…In February 2021, this program switched to a Webex platform (Cisco) 27 to accommodate synchronized, group exercise classes with up to six patients/class. Preliminary screening data from an ongoing HYCR clinical trial at Henry Ford 28 suggest that access to the needed equipment may not be a meaningful barrier in the Detroit, Michigan area, with access to a smart device and exercise equipment at 97% and 86%, respectively. 29 Another example is the CR program at the University of California-San Francisco.…”
Section: Current Use Of Hybrid Cr In Clinical Practicementioning
confidence: 99%